2011
DOI: 10.1016/j.jaridenv.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A review of runoff generation and soil erosion across scales in semiarid south-eastern Spain

Abstract: a b s t r a c tClimate, lithology, soil and especially, intense land use/cover changes, make SE Spain very vulnerable to runoff generation and water erosion leading to loss of nutrients and organic matter and to infrequent but devastating floods, reservoir siltation and mass failures. This susceptibility has led to heavy economic investment and research efforts since the 1980s, making this region a worldwide reference for understanding the hydrology and geomorphology of semiarid ecosystems. Runoff and soil ero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(138 citation statements)
references
References 65 publications
2
118
0
8
Order By: Relevance
“…Belnap (2006) suggested that differences in flora and morphology also contribute to these differences, which was confirmed by Chamizo et al (2012). According to the literature, these biocrust have runoff coefficients comparable with bare soil and larger than those from the rest of surface classes (Alexander & Calvo-Cases 1990;Cantón et al 2011;Li et al 2005;Solé-Benet et al 1997). Despite these high runoff coefficients, evidence for the ability of biocrusts to reduce erosion was found long ago, as reported by Booth (1941), who reviewed studies since 1888 and proposed a role for soil algae in controlling erosion.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Belnap (2006) suggested that differences in flora and morphology also contribute to these differences, which was confirmed by Chamizo et al (2012). According to the literature, these biocrust have runoff coefficients comparable with bare soil and larger than those from the rest of surface classes (Alexander & Calvo-Cases 1990;Cantón et al 2011;Li et al 2005;Solé-Benet et al 1997). Despite these high runoff coefficients, evidence for the ability of biocrusts to reduce erosion was found long ago, as reported by Booth (1941), who reviewed studies since 1888 and proposed a role for soil algae in controlling erosion.…”
Section: Introductionmentioning
confidence: 74%
“…Therefore, water erosion depends on rainfall erosivity (mainly determined by the amount and intensity) (Angulo-Martinez & Begueria 2009;Wei et al 2010), soil erodibility, which is controlled by the soil texture, the amount and stability of the aggregates and the organic matter content (De Baets et al 2006;Solé-Benet et al 1997) and land cover (cover, size and density of the vascular plants, of biocrusts, stones, litter) (Boix-Fayos et al 2007;Zavala et al 2009;Cantón et al 2011). Erosion also depends on topography (including surface roughness, as well as the slope angle and the size of the drainage areas) and antecedent soil moisture (Bowker et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As a core subject of soil and water conservation research in sustainable ecosystems, soil erosion is affected by various natural and human factors [1,2]. Climate, lithology, soil types, and especially intense land use/cover changes make soil vulnerable to runoff generation and water erosion, leading to the loss of nutrients from the soil, reservoir siltation, and devastating floods [3].…”
Section: Introductionmentioning
confidence: 99%
“…Lithological material is predominantly sedimentary, identified as a series of marls in contact with Miocene evaporites. Most soil is covered by Mediterranean shrubs, alternating with patches of annual grasses, biological crusts and bare surfaces (Cantón et al, 2011). The study area is on the property of the "Oro del Desierto" olive oil company, which has around 25 000 olive trees of different ages scattered on about 100 ha surrounded by scrubland and other ecological crops, such as candyleaf, almonds and grapes.…”
Section: Study Areamentioning
confidence: 99%